Translation and validation of a team viability scale for Peruvian workers - Josue Pilco-Pezo; Maribel Paredes-Saavedra; Mardel Morales-García; Liset Z. Sairitupa-Sanchez; Oriana Rivera-Lozada; Wilter C. Morales-García (Administrative Sciences, 2025)
Background: Team viability, understood as the ability to adapt and collaborate effectively over time, is a key concept in organizational literature. In Peru, where changes are constant, culturally adapted tools are needed for its measurement. Objective: To translate and validate a team viability scale for Peruvian workers. Methods: An instrumental design was used with 290 public sector employees (M = 34.61; SD = 9.2). The translation followed a cultural adaptation process, and validity was assessed through descriptive, correlational, and confirmatory factor analysis. Results: Confirmatory factor analysis supported a unidimensional structure with excellent fit indices (CFI and TLI > 0.99, RMSEA and SRMR < 0.01). The scale showed high invariance across gender and good internal consistency (» = 0.90). Conclusions: The validated scale is a reliable tool for measuring team viability in Peru. Its implementation can enhance human resource management and improve collaboration in the public sector.
Keywords: 350; cultural adaptation; factor analysis; human resources management; measurement invariance; team viability